Practitioner Profile: An Interview with Beth Crittenden - Martie Gillen (Journal of Financial Therapy, 2016)
Beth Crittenden offers financial wellness coaching to people who want growth both professionally and personally. Beth has been working with finances as a focus since 2009, after training in somatic psychology, healthy communication in relationship, and mindful meditation practices and theory.
Keywords: financial therapy; financial wellness; family business; financial consulting; money coaching